Bicycle rider control skills: expertise and assessment - Fonda, B.; Sarabon, N.; Li, F.-X. (Journal of Sports Sciences, 2017)
Research on how human balance and control bicycles are inconclusive, largely due to the small number of participants in the previous studies. Therefore, the aim of this study was to test the hypotheses that 1) cycling lateral deviation amplitude will reliably show differences between more and less experienced cyclists and 2) more experienced will exhibit slower and smaller steering motions compared to the less experienced cyclists. Twenty-eight experienced and inexperienced cyclists rode a bicycle in a straight line. Lateral deviation, steering and roll were measured. Intersession reliability of the deviation was high with Cronbach`s alpha values higher than 0.75. The amplitude, variability and rate of steering and roll parameters showed statistically significant differences between the groups. The test used in this study is sensitive to detect differences between more and less experienced cyclists and can be used for further research that aims to test the effect of a specific intervention addressing rider control. We also showed that steering and roll angle, which were described before as two of the main motor control actions in bicycle control, differ in the variability, amplitude and rate between more and less experienced cyclists. The results of the present study have practical implications for improving bicycle rider control and increasing the safety of cyclists.